Spectrum of mutations in the renin-angiotensin system genes in autosomal recessive renal tubular dysgenesis - Gribouval, Olivier; Picard, Nicole; Gaspar, Harald (Human mutation, 2012)
Autosomal recessive renal tubular dysgenesis (RTD) is a severe disorder of renal tubular development characterized by early onset and persistent fetal anuria leading to oligohydramnios and the Potter sequence, associated with skull ossification defects. Early death occurs in most cases from anuria, pulmonary hypoplasia, and refractory arterial hypotension. The disease is linked to mutations in the genes encoding several components of the renin-angiotensin system (RAS): AGT (angiotensinogen), REN (renin), ACE (angiotensin-converting enzyme), and AGTR1 (angiotensin II receptor type 1). Here, we review the series of 54 distinct mutations identified in 48 unrelated families. Most of them are novel and ACE mutations are the most frequent, observed in two-thirds of families (64.6%). The severity of the clinical course was similar whatever the mutated gene, which underlines the importance of a functional RAS in the maintenance of blood pressure and renal blood flow during the life of a human fetus. Renal hypoperfusion, whether genetic or secondary to a variety of diseases, precludes the normal development/ differentiation of proximal tubules. The identification of the disease on the basis of precise clinical and histological analyses and the characterization of the genetic defects allow genetic counseling and early prenatal diagnosis. Hum Mutat 33:316-326, 2012. © 2011 Wiley Periodicals, Inc.